Tahap kesediaan guru terhdap pelaksanaan pembelajaran berasaskan kompetensi di Kolej Vokasional - Mohd. Sukri, Nurulhuda (2013)
Transformation of Vocational Education was introduced Competency Standards (Vocational) in the format of Vocational College Curriculum Standards with Competency Based Learning (CBL) concept as the added value of the existing curriculum. Teachers are implementer agent in curriculum transformation. Generally, the involvement of teachers in curriculum innovation process provides a variety of challenges and obstacles in implementing it effectively. This study was conducted to identify the teacher’s readiness for the implementation of Competency Based Learning (CBL) in vocational colleges. The teacher’s readiness aspects that were studied have covered the aspects of knowledge, skills and attitudes of teachers in implementing the CBL. This study has involved 234 respondents from teachers who are teaching vocational modules in 15 pilot vocational colleges as a sample. Questionnaires were used as a research instrument with a value of Cronbach Alpha is 0.946 which shows the reliability of the questionnaires received. Data was analysed by descriptive in frequency, percentage, mean, standard deviation and ANOVA using SPSS Statistical Package for Social Sciences (SPSS) version 14.0. As a result, it was found that teacher’s readiness in terms of knowledge, skills and attitudes towards the implementation of CBL is moderately high with an average mean value of 3.9903 which is that indicates the teachers are willing to implement CBL in Vocational Module. The study found that there are no significant differences between the teaching experiences with the knowledge, but there are significant differences between the teaching experiences with the skills and attitudes of teachers towards the implementation of CBL.